PP.27.26: ASSOCIATIONS BETWEEN SERUM URIC ACID LEVELS AND THE INCIDENCE OF HYPERTENSION AND ATRIAL FIBRILLATION. (June 2015) - Karamanou, A.; Kallistratos, M.S.; Poulimenos, L.E.; Kouremenos, N.; Vergis, K.; Martinaios, A.; Zacharopoulou, I.; Vrakas, S.; Koukouzeli, A.; Chamodraka, E.; Siama, A.; Pagoni, S.; et al.
Abstract : Objective: Serum uric acid (SUA) is associated with many traditional cardiovascular risk factors as hypertension (HTN). Our aim was to investigate the relationship of SUA with HTN and atrial fibrillation as also the correlation of SUA with pulse wave velocity and specific diastolic echocardiographic parameters in hypertensive patients. Design and method: We prospectively enrolled 678 hypertensive patients (mean age 61.9) and 143 controls (mean age 68.3). In all subjects routine blood chemistry, including SUA determination, echocardiographic examination and 24 h ambulatory blood pressure (BP) monitoring were obtained. The group of hypertensives was divided into two subgroups: subgroup A (N = 47): hypertensives with atrial fibrillation and subgroup B (N = 631): hypertensives in sinus rhythm. We investigated the differences of SUA levels among group A, group B and the control group. In the second part we studied the correlation of SUA with left atrial diameter (LA), left ventricular mass (LVM) and pulse wave velocity (PWV) in the overall hypertensive population (N = 678). Results: Logistic regression analysis showed that increased SUA levels were significantly and positively associated with the incidence of hypertension and atrial fibrillation (group A: 9.3 ± 8.1 mg/dl vs group B: 5.2 ± 0.9 mg/dl vs control group: 4.8 ± 1 mg/dl, p < 0.001). Furthermore the ANOVA regression analysis revealed that SUA levels are significantly associated with LVM (p < 0.001) and LA (p < 0.001), while there was no significant correlation between SUA and PWV (p = NS). For a 100 mg and 10 mm increase in the LVM and LA respectively, an 0.4 mg/dl and 0.6 mg/dl on average increase in SUA was observed. Conclusions: Increased SUA levels were significantly associated with the incidence of hypertension and atrial fibrillation, while there was also a strong positive association between SUA, LVM and LA, implicating that hyperuricamia might be a novel risk factor for the LA and LV remodelling and finally for the development of atrial fibrillation.